Early Transmural Response Assessed Using Magnetic Resonance Imaging Could Predict Sustained Clinical Remission and Prevent Bowel Damage in Patients with Crohn's Disease Treated with Anti-Tumour Necrosis Factor Therapy. (13th June 2020) - Messadeg, L; Hordonneau, C; Bouguen, G; Goutorbe, F; Reimund, J M; Goutte, M; Boucher, A L; Scanzi, J; Reymond, M; Allimant, C; Dapoigny, M; Pereira, B; et al.
Abstract: Background: Magnetic resonance imaging [MRI] is a promising tool to evaluate therapeutic efficacy in ileocolonic Crohn's disease [CD]. Aims: We aimed to assess the feasibility of early MRI evaluation (week 12 [W12]) to predict corticosteroid-free remission [CFREM] at W52 and prevent long-term bowel damage. Methods: All patients with active CD needing anti-tumour necrosis factor [anti-TNF] therapy were consecutively enrolled in this multicentre prospective study. MRI was performed before starting therapy, at W12 and W52. CFREM was defined as Crohn's Disease Activity Index < 150, C-reactive protein < 5 mg/L and faecal calprotectin < 250 µg/g, with no switch of anti-TNF agents, no bowel resection and no therapeutic intensification between W12 and W52. Results: Among 46 patients, 22 [47.8%] achieved CFREM at W52. Anti-TNF agents were able to heal almost all CD lesions as soon as W12 [ p < 0.05]. Early transmural response defined as a 25% decrease of either Clermont score (odds ratio [OR] = 7.7 [1.7–34.0], p < 0.001) or Magnetic Resonance Index of Activity (OR = 4.2 [1.3–13.3], p = 0.015) was predictive of CFREM at W52. Achieving at least two items on W12-MRI among ulceration healing, disappearance of enlarged lymph nodes or sclerolipomatosis, ΔADC [apparent diffusion coefficient] > +10% or ΔRCE [relative contrast enhancement] > −30% was associated with a likelihood of CFREM at W52 of 84.6% vs 37.5% in patients without transmural response [ p < 0.001]. Early transmural response could prevent bowel damage progression over time using Clermont score (hazard ratio = 0.21 [0.0–0.9]; p = 0.037). Conclusion: Evaluation of early transmural response by MRI is feasible and is a promising end point to monitor therapeutic efficacy in patients with CD.